Badges of the Lithuanian Catholic Youth Union “Pavasaris”: Chronology, Manufacturers, Mintage and Symbols - Remecas, Eduardas (Lietuvos istorijos studijos, 2016)
The article explores badges of the Lithuanian Catholic Youth Union “Pavasaris”. The Union “Pavasaris”, the Federation from 1933, was one of the most numerous organizations in Lithuania in 1919–1940. During the entire period of its existence, the organization changed the design of its members’ badges three times: in 1920, 1925 and 1935. Different labels for men, girls, and young members were made the third time. In addition to the badges of the Organization, commemorative badges were issued as well. In 1924, the first Song Festival was held in Šiauliai, and choristers and conductors of the event were given commemorative badges.In 1927, the 2nd Song Festival was organized, and its conductors, choir leaders, and choristers were also handed out badges. In 1938, the congress was held to commemorate 25 years of the Federation. All participants of the Congress were given special commemorative badges. Moreover, the “Pavasaris” Federation produced special badges for the magazine “Pavasaris” most ardent distributors in 1934.The Union “Pavasaris” also took part in sports activities. Together along with other organizations it set up a sports organization Catholic LGSF (Lithuanian Gymnastics and Sports Federation), and the Federation purchased badges in 1929.
Keywords: badge; union „Pavasaris“